Soil function assessment in high‐mountain environments: Testing the SEPP tool in a ski resort in the Italian Alps. (8th September 2022) - Schaber, Elisabeth; D'Amico, Michele E.; Pintaldi, Emanuele; Stanchi, Silvia; Freppaz, Michele; Geitner, Clemens
Abstract: Soil function assessment (SFA) plays an important role in evaluating the impact of management practices, land‐use changes and construction work. The Soil Evaluation for Planning Procedures (SEPP) tool is one of the few existing SFA tools that allow automated SFA. It was originally developed to address land‐use planning issues, which traditionally play a minor role in high‐mountain areas. Hence, the SEPP tool has not yet been applied to such environments. In this study, we tested the SEPP performance on high‐mountain soils previously altered by construction work and land‐use changes. Specifically, we evaluated soil data from 16 ski runs and 16 paired control sites in the Italian Alps, aiming to reflect land‐use‐driven differences in soil properties in the SFA results. The study revealed options to adapt SEPP assessment methods if high‐mountain soils with special characteristics (e.g. shallowness or high coarse fragment content) are investigated. The main adaptation options are the consideration of further soil parameters and the adjustment of thresholds of function fulfilment levels. However, the assessment results of the current SEPP version already reflect the most relevant impacts of ski run construction on the soils in the study area: fulfilment of some of the soil functions was impaired and that of others improved, while most remained at a comparable level. We conclude that SFA with the SEPP tool provides valuable support for the evaluation of construction projects and land‐use change in high‐mountain environments. However, the significance of SFA can be improved by considering the intrinsic properties of high‐mountain soils.